Battery cell, battery device and electric device
By introducing a first ternary material with single-crystal particle morphology and a lithium-rich manganese-based material with secondary particle morphology into the positive electrode active material of lithium-ion batteries, and optimizing the particle size distribution, the problem of poor kinetic performance of ternary materials in the low potential range is solved, and a battery cell with high energy density and good kinetic performance is realized, reducing the dependence on rare metals and production costs.
Patent Information
- Application Number
- CN202511955703.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-07-21
- Filing Date
- 2025-12-23
- Publication Date
- 2026-01-20
AI Technical Summary
The ternary materials used in existing lithium-ion batteries have poor kinetic performance in the low potential range, resulting in low charge and discharge efficiency. Furthermore, they rely heavily on rare metal elements, which cause large price fluctuations and make it difficult to meet the needs of high-power applications and control costs.
The positive electrode active material is composed of a first ternary material in the form of single crystal particles, a second ternary material in the form of secondary particles, and a lithium-rich manganese-based material in the form of secondary particles. By controlling the particle size distribution and mass ratio of each material, a good particle size distribution relationship is formed. The introduction of lithium-rich manganese-based material provides more lithium storage sites and a wider operating voltage window, and optimizes ion transport dynamics.
It improves the charge and discharge efficiency and dynamic performance of individual battery cells, while reducing the dependence on rare metals, increasing the energy density and cycle stability of the battery, and reducing production costs.
Smart Images

Figure CN121366871A_ABST
Abstract
Description
Cross-reference to related applications
[0001] This application claims priority to international application No. PCT / CN2025 / 109675, filed on July 21, 2025, the entirety of which is incorporated herein by reference. Technical Field
[0002] This application relates to the field of battery technology, and in particular to a battery cell, a battery device, and an electrical device. Background Technology
[0003] Batteries are widely used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. As the application scope of batteries expands, the requirements for battery performance are becoming increasingly stringent. Summary of the Invention
[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a battery cell that further improves the dynamic performance of the battery cell on the basis of having high energy density.
[0005] To achieve the above objectives, a first aspect of this application provides a battery cell, including a positive electrode sheet, the positive electrode sheet comprising: a positive current collector; a positive electrode film layer located on at least one side of the positive current collector; the positive electrode film layer comprising a positive electrode active material, the positive electrode active material comprising a ternary material and a lithium-rich manganese-based material; the ternary material comprising a first ternary material having a single-crystal particle morphology and a second ternary material having a secondary particle morphology, the lithium-rich manganese-based material being in a secondary particle morphology; the mass ratio of the first ternary material to the second ternary material in the positive electrode film layer is 1:(1-9).
[0006] This application includes at least the following beneficial effects: The positive electrode active material in this application combines a first ternary material with a single-crystal particle morphology, a second ternary material with a secondary particle morphology, and a lithium-rich manganese-based material with a secondary particle morphology to form a favorable particle size distribution. Simultaneously, the lithium-rich manganese-based material with a secondary particle morphology provides more lithium storage sites and a wider operating voltage window, improving ion transport kinetics in the low-potential range, enabling the battery cell to possess both high energy density and good kinetic performance. Furthermore, by controlling the mass ratio of single-crystal ternary material particles to secondary particles in the positive electrode film, not only can the battery cell possess both kinetic and cycle performance, but a favorable particle size distribution can also be formed to improve the battery's compaction density, thereby further increasing the battery's energy density.
[0007] In some embodiments, the average particle size of the first ternary material is 1.5 pm to 3 pm. The smaller the average particle size of the single crystal particles, the shorter the migration path of lithium ions, and the better the kinetic performance of the battery cell. At the same time, the particle size of the single crystal particles also needs to be controlled to be greater than or equal to 1.5 pm to meet the requirements of the particle size distribution of the positive electrode active material. In this way, by controlling the average particle size of the first ternary material, the kinetic performance and energy density of the battery cell can be further balanced.
[0008] In some embodiments, the average particle size of the second ternary material is 5 pm to 15 pm. The larger the average particle size of the secondary particles, the more primary particles they contain, and the better the kinetic performance of the battery cell. At the same time, the average particle size of the secondary particles also needs to be controlled to be less than or equal to 15 pm to reduce the risk of primary particles falling off in the secondary particles, to reduce the occurrence of side reactions, and thus to improve the electrochemical performance of the battery cell. In addition, the average particle size of the secondary particles also needs to meet the requirements of the particle size distribution of the positive electrode active material. In this way, by controlling the average particle size of the second ternary material, the electrochemical performance, kinetic performance, and energy density of the battery cell can be further balanced.
[0009] In some embodiments, the average particle size of the primary particles in the lithium-rich manganese-based material is 150 nm to 350 nm. Controlling the average particle size of the primary particles in the lithium-rich manganese-based material not only increases the specific surface area of the material to increase the lithium ion deintercalation interface, effectively reduces the interface transmission impedance of lithium ions, and thus optimizes the kinetic performance of the battery cell, but also reduces the side reactions caused by too small primary particles and too large specific surface area, and thus improves the cycle performance of the battery cell. In this way, by controlling the average particle size of the primary particles in the lithium-rich manganese-based material to be in the range of 150 nm to 350 nm, the kinetic performance and cycle performance of the battery cell can be further balanced.
[0010] In some embodiments, the average particle size of the primary particles in the lithium-rich manganese-based material is 200 nm to 300 nm. In this way, the kinetic performance and cycle performance of the battery cell can be further balanced.
[0011] In some embodiments, the average particle size of the lithium-rich manganese-based material is 6 pm to 12 pm. The larger the average particle size of the lithium-rich manganese-based material, the more secondary particles it can contain, and the better the kinetic performance of the battery cell. At the same time, the average particle size of the lithium-rich manganese-based material also needs to be controlled to be less than or equal to 12 pm to meet the requirements of the particle size distribution of the positive electrode active material. In this way, by controlling the average particle size of the lithium-rich manganese-based material, the energy density and kinetic performance of the battery cell can be balanced.
[0012] In some embodiments, the positive electrode active material satisfies one or both of the following conditions: the Dv50 particle size of the positive electrode active material in the positive electrode film layer is 3-15 μm; the (Dv90-Dv10) / Dv50 of the positive electrode active material in the positive electrode film layer is 1.6-2. In this way, the battery cell can have high energy density, good kinetic performance and safety performance.
[0013] In some embodiments, the positive electrode active material satisfies one or both of the following conditions: the Dv50 particle size of the positive electrode active material in the positive electrode film layer is 5-10 μm; the (Dv90-Dv10) / Dv50 of the positive electrode active material in the positive electrode film layer is 1.7-1.9. In this way, the comprehensive performance of the battery cell can be further optimized.
[0014] In some embodiments, the mass ratio of the lithium-rich manganese-based material to the ternary material is 1:(1-49). In this way, by controlling the mass ratio of the lithium-rich manganese-based material to the ternary material, not only can the kinetic performance of the battery cell be improved by means of the lithium-rich manganese-based material, but also the problems of lattice distortion, cation mixing and micro-crack generation during the cycle process can be reduced by relying on the better intrinsic crystal structure stability of the ternary material, so that the battery cell can maintain good structural stability and good cycle performance in long-term cycling.
[0015] In some embodiments, the lithium-rich manganese-based material satisfies the chemical formula X·Li2MnO3+(1-X)·Li a1 Ni b1 Mn d1 M1 e1 O2; wherein 0.4≤X<1.0, b1 is 0.2-0.7, d1 is 0.3-0.8, e1 is 0-0.5, b1+d1+e1=1, a1 is 0.6-1.2, and M1 includes one or more elements from Group IA, Group II A, Group III A, Group IV A, Group VA, Group VIA, Group VIII, Group IB, Group III B, Group IV B, Group VB and Group VIB. In this way, these lithium-rich manganese-based materials can optimize the kinetic performance of the battery cell.
[0016] In some embodiments, the lithium-rich manganese-based material satisfies one or both of the following conditions: X is 0.6-0.8, b1 is 0.3-0.6, d1 is 0.5-0.7, and e1 is 0-0.2; and M1 includes one or more elements from Co, Al, Mg, Sr, B, S, Ca, Na, Sn, Cu, Ti, Nb, La, Bi, Zr, Ga, W, V, Zn, In and Ru. In this way, these lithium-rich manganese-based materials can further optimize the kinetic performance of the battery cell.
[0017] In some embodiments, the lithium-rich manganese-based material comprises a core and a coating layer covering at least part of the surface of the core; the coating layer comprises one or more of a fast ion conductor material, an aluminum-based inorganic substance. In this way, the core structure can be effectively protected, and the reasonable length of ion diffusion path can be maintained to further balance the electrochemical performance and kinetic performance of the battery.
[0018] In some embodiments, the thickness of the coating layer is 0.1 μm-1 μm. In this way, the thickness of the coating layer is controlled in the range of 0.1 μm-1 μm, which can effectively protect the core structure and maintain the reasonable length of ion diffusion path to further balance the electrochemical performance and kinetic performance of the battery cell.
[0019] In some embodiments, the coating layer satisfies one or both of the following conditions: the fast ion conductor material comprises one or more of lithium silicate, lithium nitride, lithium borate, lithium fluoride, lithium carbonate, lithium hydroxide, lithium phosphate, lithium zirconate, lithium sulfate, lithium iodate, lithium sulfide, lithium phosphide, lithium acetate, lithium chloride, lithium bromide, lithium iodide, lithium phosphorus sulfide; the aluminum-based inorganic substance comprises one or more of aluminum oxide, magnesium aluminum spinel, calcium aluminate, aluminum phosphate, aluminum borate, aluminum silicate, aluminum fluoride, sodium hexafluoroaluminate, titanium dialuminate, aluminum carbide.
[0020] In some embodiments, the first ternary material and the second ternary material each independently satisfy the chemical formula Li a2 Ni b2 Co c2 Mn d2 M2 e2 O f , wherein a2 is 0.6-1.1, b2 is 0.5-0.95, c2 is 0.01-0.25, d2 is 0.01-0.35, e2 is 0.001-0.01, f is 1.9-2.1, b2+c2+d2+e2=1, M2 comprises one or more of Al, Mg, Sr, B, Ca, Na, K, Sn, Cu, Ti, Nb, La, Bi, Zr.
[0021] In some embodiments, the first ternary material and the second ternary material each independently satisfy one or both of the following conditions: b2 is 0.8-0.9, c2 is 0.01-0.09, d2 is 0.01-0.19; M2 comprises one or more of Al, Mg, Sr, B, Na, K, Sn, Ti.
[0022] In some embodiments, the first and second ternary materials each independently satisfy a molar ratio of nickel element to manganese element of (3-18): 1. In this way, the increase of nickel content can increase the reversible lithium intercalation capacity of the ternary material, thereby increasing the energy density of the battery cell; at the same time, by controlling the molar ratio of nickel element to manganese element, the manganese element can inhibit cation mixing, stabilize the layered structure, and has a price advantage, so that the safety performance and control cost of the battery cell can be improved on the basis of high energy density.
[0023] In some embodiments, the second ternary material satisfies one or more of the following conditions: the molar content of nickel element in the second ternary material is higher than the molar content of nickel element in the first ternary material; the molar content of cobalt element in the second ternary material is higher than the molar content of cobalt element in the first ternary material; the molar content of manganese element in the second ternary material is lower than the molar content of manganese element in the first ternary material. In this way, for the second ternary material (secondary particles), high nickel content can significantly increase the lithium storage sites of the second ternary material, which can increase the energy density of the battery cell; high cobalt content can enhance the stability and electronic conductivity of the layered structure of the second ternary material, making up for the problem of increased resistance caused by more inter-particle contact interfaces of the secondary particles, thereby improving the kinetic performance of the battery cell; for the first ternary material (single crystal particles), the manganese element has a stable crystal structure, which can give the single crystal particles stronger structural stability, which is consistent with the characteristics of the single crystal particles themselves, i.e., no inter-particle grain boundaries and more emphasis on providing long cycle stability; at the same time, the relatively low nickel content and cobalt content ratio in the first ternary material can also balance the production cost and overall stability of the battery cell on the premise of having basic performance.
[0024] In some embodiments, the positive electrode film layer has a compaction density of 3.4 g / cm3 under 5000 kg. 3 -3.7 g / cm3 3 In this way, the battery cell can have higher energy density.
[0025] In some embodiments, the positive electrode sheet satisfies one or both of the following conditions: the thickness of the positive electrode current collector is 10-15 μm; the single-sided thickness of the positive electrode film layer is 30-60 μm. In this way, this thickness range can cover conventional 2C to 4C ternary battery design.
[0026] In a second aspect of the present application, the present application provides a battery device comprising a plurality of battery cells of the first aspect of the present application.
[0027] In a third aspect of the present application, the present application provides a power utilization device comprising a battery cell of the first aspect of the present application or a battery device of the second aspect of the present application. BRIEF DESCRIPTION OF DRAWINGS
[0028] Figure 1 is a schematic view of a battery cell according to an embodiment of the present application.
[0029] Figure 2 is Figure 1 is an exploded view of a battery cell according to an embodiment of the present application.
[0030] Figure 3 is a schematic view of a battery module according to an embodiment of the present application.
[0031] Figure 4 is a schematic view of a battery pack according to an embodiment of the present application.
[0032] Figure 5 is Figure 4 is an exploded view of a battery pack according to an embodiment of the present application.
[0033] Figure 6 is a schematic view of an electric device using a battery cell according to an embodiment of the present application as a power source.
[0034] Figure 7 is a scanning electron microscope image of the lithium-rich manganese-based material particles in Example 1.
[0035] Figure 8 is Figure 7 is a partial enlarged view of the A region in
[0036] BRIEF DESCRIPTION OF DRAWINGS 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 battery cell; 51 case; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0037] Hereinafter, embodiments of a battery cell, a battery device, and an electric device according to the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there will be cases where unnecessary detailed description is omitted. For example, there will be cases where detailed description of matters that are well known, repeated description of substantially identical structures are omitted. This is to avoid the following description becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the drawings and the following description are provided so that those skilled in the art can fully understand the present application, and are not intended to limit the subject matter recited in the claims.
[0038] The ranges disclosed herein are intended to be "open" ranges, i.e., the upper and lower limits of the range are not included. The ranges are also intended to include any and all sub-ranges of the same, wherein each sub-range is inclusive of the end values. For example, if a range is from 1 to 10, then the range includes any and all sub-ranges between (and including) the minimum of 1 and the maximum of 10, that is, any of 1 to 3, 4 to 6, 7 to 9, and 3 to 7, etc. Also, it is specifically intended that the minimum and maximum values of the ranges are included in the ranges. For example, if a parameter is stated to be from 1 to 10, it is specifically intended that the parameter can be 1 - 10, 1 - 3, 4 - 6, 7 - 9, 3 - 7, etc. In the present application, unless otherwise indicated, the numerical values of ranges "a-b" are intended to include any and all sub-ranges of said range, wherein each sub-range is inclusive of the end values. For example, a range of "0-5" is intended to include any and all sub-ranges between (and including) the minimum of 0 and the maximum of 5, that is, any of 0-3, 4-5, 0- 1, 2- 4, 3- 5, 0- 5, etc. Also, it is specifically intended that the minimum and maximum values of the ranges are included in the ranges. For example, a range of "a-b" is intended to include "a" and "b". Also, it is specifically intended that the parameter can be "a" or "b", or "a-b". For example, if a parameter is stated to be from 1 to 10, it is specifically intended that the parameter can be 1 - 10, 1, 10, 3.4, etc.
[0039] All embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, if not specifically stated otherwise.
[0040] All technical features and optional technical features of the present application can be combined with each other to form new technical solutions, if not specifically stated otherwise.
[0041] All steps of the present application can be performed in sequence or randomly, preferably in sequence, if not specifically stated otherwise. For example, the method comprises steps (a) and (b) means that the method can comprise steps (a) and (b) in sequence, or steps (b) and (a) in sequence. For example, the method further comprises step (c) means that step (c) can be added to the method in any sequence, for example, the method can comprise steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0042] With the rapid development of new energy vehicles, portable electronic devices, energy storage systems and other fields, higher requirements are put forward for the comprehensive performance of batteries. As a commonly used positive active material of lithium ion batteries, ternary material occupies an important position in the market due to its advantages such as high energy density and good cycle stability. However, the working voltage window of ternary material (2.8V-4.4V) is relatively narrow, and the battery has poor dynamic performance when discharging in the low potential interval, resulting in low battery charge and discharge efficiency and insufficient power density, which is difficult to meet the rapid charge and discharge requirements in high-power scenarios. In addition, ternary material is highly dependent on rare metal elements such as cobalt and nickel, and the price fluctuation range of cobalt and nickel raw materials is large, which limits the large-scale application of ternary material.
[0043] Based on this, the first aspect of the present application provides a battery monomer, comprising a positive electrode sheet, the positive electrode sheet comprising: a positive electrode current collector; a positive electrode film layer located on at least one side of the positive electrode current collector; the positive electrode film layer comprises a positive electrode active material, the positive electrode active material comprises a ternary material and a lithium-rich manganese-based material; the ternary material comprises a first ternary material having a single crystal particle morphology and a second ternary material having a secondary particle morphology, and the lithium-rich manganese-based material has a secondary particle morphology; the mass ratio of the first ternary material to the second ternary material in the positive electrode film layer is 1:(1-9).
[0044] Therefore, the introduction of lithium-rich manganese-based material with higher specific capacity and more advantageous price in the positive electrode film layer not only can guarantee the energy density of the battery monomer and reduce the dependence on rare metal elements; more importantly, the lithium-rich manganese-based material has a wider working voltage window (2.0V-4.8V) than the ternary material, and when the ternary material is in the discharge end period, the lithium-rich manganese-based material still has more lithium storage sites, which can provide an additional lithium ion transmission path to improve the ion transmission dynamics in the low potential interval, thereby improving the charge and discharge efficiency of the battery monomer to improve the dynamic performance of the battery monomer.
[0045] The secondary particle morphology of the lithium-rich manganese-based material refers to an agglomerate formed by agglomeration of a plurality of primary particles of the lithium-rich manganese-based material, which has a larger specific surface area. Among them, the primary particle refers to the initial fine particle formed during the crystallization process of the material, and the secondary particle is formed by sintering a plurality of primary particles. Therefore, the lithium-rich manganese-based material in secondary particle morphology can provide more lithium storage sites to further improve the ion transmission dynamics in the low potential interval, thereby further optimizing the dynamic performance of the battery monomer.
[0046] In the present application, the first ternary material in the form of single crystal particles refers to the smallest unit of particles in the ternary material within a certain observation range, which is a single crystalline unit at the microscale. It should be noted that the single crystal particles here do not necessarily mean that there is no grain boundary inside the single crystal, nor are they strictly limited to the continuous and consistent periodic arrangement of atoms, molecules or ions in three-dimensional space. Instead, they refer to particles that cannot be further divided by grain boundaries within the single crystal at a certain observation scale. The first ternary material in the form of single crystal particles has the characteristics of small particle size and good structural stability, which can reduce particle breakage caused by volume changes during charging and discharging cycles, and improve the cycle stability of the battery cell.
[0047] The second ternary material in the form of secondary particles refers to a ternary material particle formed by agglomeration of multiple primary particles. The second ternary material in the form of secondary particles has the characteristics of a large specific surface area, which increases the interface for lithium ion deintercalation, improves the surface reaction activity, and reduces the interface transmission impedance of lithium ions, thereby improving the kinetic performance of the battery cell.
[0048] Therefore, on the basis of introducing the lithium-rich manganese-based material in the form of secondary particles, the positive electrode film layer of the present application further uses the first ternary material in the form of single crystal particles in combination with the second ternary material in the form of secondary particles. At the same time, by controlling the mass ratio of the single crystal particles and the secondary particles of the ternary material in the positive electrode film layer, not only can the kinetic performance and cycle performance of the battery be further improved, but also a good particle size grading relationship can be formed to improve the compaction density of the battery, thereby further improving the energy density of the battery.
[0049] In summary, in the present application, the positive electrode active material adopts a combination of the first ternary material in the form of single crystal particles, the second ternary material in the form of secondary particles, and the lithium-rich manganese-based material in the form of secondary particles, forming a good particle size grading relationship. At the same time, the lithium-rich manganese-based material in the form of secondary particles can provide more lithium storage sites and a wider operating voltage window, improve the ion transport dynamics in the low potential range, and enable the battery cell to have both high energy density and good kinetic performance.
[0050] In the present application, the first ternary material, the second ternary material, and the lithium-rich manganese-based material in the form of secondary particles in the positive electrode film layer can be determined in the following manner. As an example, a cross-section in the thickness direction of the positive electrode tab is obtained, and particles in any 10 regions of the same size and shape in the same scanning electron microscope (SEM) image under 10000 times magnification are observed. The materials in the form of single crystal particles and the materials in the form of secondary particles can be directly distinguished by the scanning electron microscope image; then, energy dispersive spectroscopy (EDS) element analysis of the scanning electron microscope image can further analyze the second ternary material in the form of secondary particles and the lithium-rich manganese-based material in the form of secondary particles.
[0051] Of course, those skilled in the art can understand that the first ternary material, the second ternary material, and the lithium-rich manganese-based material with a secondary particle morphology in the positive electrode film layer in the present application can also be determined by using instruments and methods known in the art.
[0052] In the present application, the mass ratio of the first ternary material and the second ternary material in the positive electrode film layer can be determined in the following manner. For example, the relative content of elements of the positive electrode active material as a whole can be tested by using electron spectroscopy (EDS) on at least 5 cross-sectional areas (for example, 100 μm x 100 μm) of the positive electrode tab, and the average value is obtained; then the components of a single crystal particle, a secondary particle, and a lithium-rich manganese-based particle are tested respectively; and according to the relative content of the characteristic elements, the mass ratio of the single crystal particle to the secondary particle can be calculated.
[0053] Those skilled in the art can understand that the mass ratio of the first ternary material and the second ternary material in the positive electrode film layer can also be determined by using instruments and methods known in the art.
[0054] As an example, the mass ratio of the first ternary material to the second ternary material in the positive electrode film layer can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc., or a range composed of any two of the above values.
[0055] In some embodiments, the average particle size of the first ternary material is 1.5 μm-3 μm.
[0056] The smaller the average particle size of the single crystal particle, the shorter the migration path of lithium ions, and the better the kinetic performance of the battery monomer. At the same time, the particle size of the single crystal particle also needs to be controlled to be greater than or equal to 1.5 μm, so that the particle size of the single crystal particle meets the requirements of the particle size distribution of the positive electrode active material. In this way, by controlling the average particle size of the first ternary material, the kinetic performance and energy density of the battery monomer can be further balanced.
[0057] As an example, the average particle size of the first ternary material can be 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, etc., or a range composed of any two of the above values.
[0058] In some embodiments, the average particle size of the second ternary material is 5 μm-15 μm.
[0059] The larger the average particle size of the secondary particles, the more primary particles the secondary particles contain, and the better the kinetic performance of the battery cell. Meanwhile, the average particle size of the secondary particles needs to be controlled to be less than or equal to 15 μm, so as to reduce the risk of the primary particles falling off from the secondary particles and reduce the occurrence of side reactions, thereby improving the electrochemical performance of the battery cell. In addition, the average particle size of the secondary particles also needs to meet the particle size distribution requirement of the positive active material. Therefore, by controlling the average particle size of the second ternary material, the electrochemical performance, kinetic performance and energy density of the battery cell can be further balanced.
[0060] For example, the average particle size of the second ternary material can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range formed by any two of the above values.
[0061] In some embodiments, the average particle size of the primary particles in the lithium-rich manganese-based material is 150 nm-350 nm.
[0062] In this application, the primary particles in the lithium-rich manganese-based material refer to the smallest unit within a certain identification range. The primary particles can include any form of defects inside, but it is not possible to further define smaller particles in the primary particles. The aggregation of the primary particles is called secondary particles. The secondary particles have a clear surface and boundary, but after cutting the cross section of the secondary particles, it can be seen that the secondary particles are formed by the aggregation of a large number of primary particles.
[0063] Controlling the average particle size of the primary particles in the lithium-rich manganese-based material can not only increase the specific surface area of the material to increase the lithium ion deintercalation interface, thereby effectively reducing the interface transmission impedance of lithium ions and optimizing the kinetic performance of the battery cell, but also reduce the side reactions caused by too small primary particles and too large specific surface area, thereby improving the cycle performance of the battery cell.
[0064] Therefore, by controlling the average particle size of the primary particles in the lithium-rich manganese-based material to be in the range of 150 nm-350 nm, the kinetic performance and cycle performance of the battery cell can be further balanced.
[0065] For example, the average particle size of the primary particles in the lithium-rich manganese-based material can be 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm, 310 nm, 320 nm, 330 nm, 340 nm, 350 nm, or a range formed by any two of the above values. In some other embodiments of the application, the average particle size of the primary particles in the lithium-rich manganese-based material is 200 nm-300 nm.
[0066] In some embodiments, the average particle size of the lithium-rich manganese-based material is 6 μm-12 μm.
[0067] In the present application, the average particle size of the lithium-rich manganese-based material refers to the average particle size of the secondary particles of the lithium-rich manganese-based material. The larger the average particle size of the lithium-rich manganese-based material, the more secondary particles it can contain, and the better the kinetic performance of the battery cell. At the same time, the average particle size of the lithium-rich manganese-based material needs to be controlled to be less than or equal to 12 μm, so that the particle size of the lithium-rich manganese-based material meets the requirements of the particle size distribution of the positive active material. In this way, controlling the average particle size of the lithium-rich manganese-based material can balance the energy density and kinetic performance of the battery cell.
[0068] For example, the average particle size of the lithium-rich manganese-based material can be 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or a range consisting of any two of the above values.
[0069] Those skilled in the art can understand that in the present application, the average particle size of the first ternary material, the average particle size of the second ternary material, the average particle size of the lithium-rich manganese-based material, and the average particle size of the primary particles in the lithium-rich manganese-based material in the positive electrode film layer can be measured by instruments and methods known in the art.
[0070] In the present application, the average particle size of the first ternary material, the average particle size of the first ternary material, and the average particle size of the secondary particles of the lithium-rich manganese-based material can be measured by the following method. For example, a cross-section in the thickness direction of the positive electrode sheet is obtained, and 10 particles of the same size and shape in the same scanning electron microscope (SEM) image under 10000 times magnification are observed. Then, the 10 regions are each subdivided into four corners and a center, a total of 5 positions, and one first ternary material particle, one second ternary material particle, and one secondary particle of the lithium-rich manganese-based material are selected from each position under the same magnification. The average particle size of each type of particle is obtained by averaging the particle size results of the four corners and the center of the 5 positions, and then the average particle size of each type of particle is obtained by averaging the particle size of each type of particle in the 10 regions.
[0071] It can be understood that the particle size of each type of particle refers to the diameter of the equivalent circle of the particle as the particle size of the particle.
[0072] In the present application, the average particle size of the primary particles of the lithium-rich manganese-based material can be determined by the following method. As an example, a cross-section in the thickness direction of the positive electrode sheet is obtained, and any 10 regions with the same size and shape in the same scanning electron microscope (SEM) image under 30000 times magnification are observed. Then, the 10 regions are each subdivided into four corners and a center, a total of 5 positions, and the particle size of any one primary particle at each position under the magnification is selected, and the particle size results at the four corners and the center, a total of 5 positions, are averaged to obtain the average particle size of the primary particles in the region. Then, the particle sizes of the primary particles obtained from the 10 regions are averaged to obtain the average particle size of the primary particles. The diameter of the equivalent circle of each particle is taken as the particle size of the particle.
[0073] In some embodiments, the positive electrode active material satisfies one or both of the following conditions: the Dv50 particle size of the positive electrode active material in the positive electrode film layer is 3-15 μm; and the (Dv90-Dv10) / Dv50 of the positive electrode active material in the positive electrode film layer is 1.6-2.
[0074] In the present application, the Dv10, Dv50, and Dv90 particle sizes of the positive electrode active material represent the particle size corresponding to the volume distribution percentage of 10%, 50%, and 90%, respectively, of the particles according to the particle size volume distribution.
[0075] From the aspect of processability, controlling the Dv50 particle size of the positive electrode active material can not only reduce the case where the proportion of large-particle positive electrode active material is too high, thereby reducing the problem of the positive electrode current collector being damaged due to the large force exerted by the large-particle positive electrode active material on the positive electrode current collector during cold pressing of a battery monomer that often requires a thin positive electrode coating thickness to adapt to fast charging performance, thereby helping to improve the yield and safety performance of the product; at the same time, positive electrode active material particles of suitable size can help to form a tightly packed structure during cold pressing, thereby increasing the compaction density of the positive electrode sheet, and further increasing the energy density of the battery monomer.
[0076] From the aspect of electrochemical performance, controlling the Dv50 particle size of the positive electrode active material can reduce the case where the proportion of small-particle positive electrode active material is too high, thereby reducing the problem of the cycle life of the battery monomer being reduced due to the poor cycle stability of small-size positive electrode active material particles; at the same time, it can also reduce the agglomerates formed by the agglomeration of small-particle positive electrode active material due to high surface energy, thereby helping to improve the dispersion of the slurry and the uniformity of the distribution of the conductive agent, and further improving the ion transport and electron conduction efficiency, to further optimize the kinetic performance of the battery monomer.
[0077] For example, the Dv50 particle size of the positive electrode active material in the positive electrode film layer can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or the like, or a range defined by any two of the above values.
[0078] In the present application, (Dv90-Dv10) / Dv50 represents the difference in particle size distribution of the positive electrode active material. The greater the (Dv90-Dv10) / Dv50, the wider the particle size distribution of the positive electrode active material, and the more significant the difference between large particles and small particles. In this case, it is difficult to form a close-packed structure between particles, which leads to difficulty in improving the compaction density of the positive electrode film layer. On the other hand, the smaller the (Dv90-Dv10) / Dv50, the more concentrated the particle size distribution, and the lack of necessary particle size gradation and small particles to fill the gaps between large particles, which is also not conducive to forming a close-packed structure.
[0079] In the present application, by controlling the (Dv90-Dv10) / Dv50 of the positive electrode active material in the range of 1.6-2, a reasonable particle size gradation can be constructed. Small particles can fill the gaps between large particles to form a more close-packed structure, reduce the inter-particle porosity, thereby improving the compaction density of the positive electrode sheet, and further improving the energy density of the battery cell.
[0080] For example, the (Dv90-Dv10) / Dv50 of the positive electrode active material in the positive electrode film layer can be 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2, or the like, or a range defined by any two of the above values. In some embodiments, the (Dv90-Dv10) / Dv50 of the positive electrode active material in the positive electrode film layer is 1.7-1.9.
[0081] In the present application, the Dv10, Dv50, and Dv90 particle sizes of the positive electrode active material can be measured by instruments and methods known in the art. For example, a laser particle size analyzer (such as Malvern Master Size 3000) can be used for measurement. It should be noted that the Dv10, Dv50, and Dv90 particle sizes of the positive electrode active material in the present application can be obtained by stripping the positive electrode film layer from the positive electrode sheet, dissolving other materials with a solvent, and then measuring the Dv10, Dv50, and Dv90 particle sizes of the positive electrode active material by a laser particle size analyzer. Alternatively, the Dv10, Dv50, and Dv90 particle sizes of the positive electrode active material powder can be directly measured.
[0082] In some embodiments, the lithium-rich manganese-based material and the ternary material satisfy one or both of the following conditions: the Dv50 particle size of the lithium-rich manganese-based material in the positive electrode film layer is 5-10 μm; the (Dv90-Dv10) / Dv50 of the lithium-rich manganese-based material in the positive electrode film layer is 1.7-1.9. In this way, the comprehensive performance of the battery cell can be further optimized.
[0083] In some embodiments, the mass ratio of the lithium-rich manganese-based material to the ternary material is 1:(1-49).
[0084] In this way, by controlling the mass ratio of the lithium-rich manganese-based material to the ternary material, not only can the kinetic performance of the battery cell be improved by means of the lithium-rich manganese-based material, but also the problems of lattice distortion, cation mixing and micro-crack generation during the cycle process can be reduced by relying on the better intrinsic crystal structure stability of the ternary material, so that the battery cell maintains good structural stability and good cycle performance in long-term cycling.
[0085] The mass ratio of the lithium-rich manganese-based material to the ternary material in the positive electrode film layer can be determined by the following method. Specifically, first, the positive electrode film layer powder is scraped from the positive electrode current collector, and the total mass of the positive electrode film layer powder is tested; then the positive electrode film layer powder is digested using a mixed solution of concentrated nitric acid and concentrated hydrochloric acid to obtain a mixed solution; the mixed solution is introduced into an inductively coupled plasma emission spectrometer, and the contents of characteristic elements such as Ni, Co and Mn can be measured; according to the contents of these characteristic elements, combined with the chemical formula of the lithium-rich manganese-based material and the ternary material respectively, the mass ratio of the two is calculated by establishing an element conservation equation. It can be understood that those skilled in the art can also use instruments and methods known in the art to determine.
[0086] As an example, the mass ratio of the lithium-rich manganese-based material to the ternary material can be 1:1, 1:3, 1:5, 1:7, 1:9, 1:11, 1:13, 1:15, 1:17, 1:19, 1:21, 1:23, 1:25, 1:27, 1:29, 1:31, 1:33, 1:35, 1:37, 1:39, 1:41, 1:43, 1:45, 1:47, 1:49, etc., or a range composed of any two of the above values.
[0087] In some embodiments, the lithium-rich manganese-based material satisfies the chemical formula X·Li2MnO3+(1-X)·Li a1 Ni b1 Mn d1 M1 e1O2; wherein, 0.4≤X<1.0, b1 is 0.2-0.7, d1 is 0.3-0.8, e1 is 0-0.5, b1+d1+e1=1, a1 is 0.6-1.2, M1 includes one or more elements of Group IA, Group II A, Group III A, Group IV A, Group VA, Group VIA, Group VIII, Group IB, Group III B, Group IV B, Group VB, Group VI B. Thus, these lithium-rich manganese-based materials can optimize the kinetic performance of the battery cell.
[0088] As an example, X can be 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, etc., or a range between any two of the above values.
[0089] As an example, b1 can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, etc., or a range between any two of the above values.
[0090] As an example, d1 can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc., or a range between any two of the above values.
[0091] As an example, e1 can be 0, 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.5, etc., or a range between any two of the above values.
[0092] As an example, a1 can be 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, etc., or a range between any two of the above values.
[0093] As an example, the Group IA element can include Na.
[0094] As an example, the Group II A element can include Mg, Sr, Ca.
[0095] As an example, the Group III A element can include Al, B, Ga, In.
[0096] As an example, the Group IV A element can include Sn.
[0097] As an example, the Group VA element can include Bi.
[0098] As an example, the Group VIA element can S.
[0099] As an example, the Group VIII element can include Co, Ru.
[0100] As an example, the Group IB element can include Cu, Zn.
[0101] As an example, the Group III B element can include La.
[0102] As an example, the Group IV B element can include Ti, Zr.
[0103] As an example, the Group V B element can include V, Nb.
[0104] As an example, the Group VI B element can include W.
[0105] In some embodiments, the lithium-rich manganese-based material satisfies one or both of the following conditions: X is 0.6-0.8, b1 is 0.3-0.6, d1 is 0.5-0.7, e1 is 0-0.2; M1 includes one or more of Co, Al, Mg, Sr, B, S, Ca, Na, Sn, Cu, Ti, Nb, La, Bi, Zr, Ga, W, V, Zn, In, Ru. Thus, these lithium-rich manganese-based materials can further optimize the kinetic performance of the battery cell.
[0106] In some embodiments, the lithium-rich manganese-based material includes a core and a coating layer, the coating layer covering at least part of the surface of the core; the coating layer includes one or more of a fast ion conductor material, an aluminum-based inorganic material.
[0107] In this application, the coating layer refers to the part coated on the core, which can but does not necessarily completely coat the core.
[0108] Due to the insufficient intrinsic crystal structure stability of the lithium-rich manganese-based material, the volume expansion amplitude of the lithium-rich manganese-based material is large during the charging and discharging process of the battery cell. For the lithium-rich manganese-based material with primary particles, the repeated expansion / contraction of the volume in the charging and discharging cycle will accumulate mechanical stress at the interface between the primary particles. When the stress exceeds the bonding strength between the primary particles, the primary particles are prone to fall off. This process can trigger the side reaction of the electrolyte and the active material, leading to the loss of active material and rapid capacity decay. The coating layer forms a protective layer on the surface of the core, which can buffer the stress generated by the volume change through mechanical support, effectively inhibit the falling off of the primary particles, reduce the occurrence of side reactions, and thus improve the cycle stability of the battery cell.
[0109] The fast ion conductor material can further improve the lithium conductivity of the lithium-rich manganese-based material to further improve the kinetic performance of the battery cell; the aluminum-based inorganic material can further improve the mechanical stability of the coating layer to further inhibit the falling off of the primary particles to further improve the cycle stability of the battery cell.
[0110] In some embodiments, the thickness of the coating layer is 0.1 μm-1 μm.
[0111] Therefore, the thickness of the coating layer is controlled in the range of 0.1 μm-1 μm, which can effectively protect the core structure and maintain a reasonable length of ion diffusion path to further balance the electrochemical performance and kinetic performance of the battery cell.
[0112] In the present application, the thickness of the coating layer refers to the thickness of the part coated on the core along the normal direction of the core.
[0113] In the present application, the thickness of the coating layer can be measured by observing the lattice fringes on the crystal surface of the coating layer through a transmission electron microscope (TEM). It can be understood that those skilled in the art can also use instruments and methods known in the art to determine.
[0114] For example, the thickness of the coating layer can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, etc., or a range consisting of any two of the above values.
[0115] In some embodiments, the coating layer satisfies one or both of the following conditions: the fast ion conductor material includes one or more of lithium silicate, lithium nitride, lithium borate, lithium fluoride, lithium carbonate, lithium hydroxide, lithium phosphate, lithium zirconate, lithium sulfate, lithium iodate, lithium sulfide, lithium phosphide, lithium acetate, lithium chloride, lithium bromide, lithium iodide, lithium phosphorus sulfide; the aluminum-based inorganic material includes one or more of aluminum oxide, magnesium aluminum spinel, calcium aluminate, aluminum phosphate, aluminum borate, aluminum silicate, aluminum fluoride, sodium hexafluoroaluminate, titanium dialuminate, aluminum carbide.
[0116] In some embodiments, the first ternary material and the second ternary material each independently satisfy the chemical formula Li a2 Ni b2 Co c2 Mn d2 M2 e2 O f , wherein a2 is 0.6-1.1, b2 is 0.5-0.95, c2 is 0.01-0.25, d2 is 0.01-0.35, e2 is 0.001-0.01, f is 1.9-2.1, b2+c2+d2+e2=1, M2 includes one or more of Al, Mg, Sr, B, Ca, Na, K, Sn, Cu, Ti, Nb, La, Bi, Zr.
[0117] For example, a2 can be 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, etc., or a range consisting of any two of the above values.
[0118] As an example, b2 can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, etc., or a range between any two of the above values.
[0119] As an example, c2 can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, etc., or a range between any two of the above values.
[0120] As an example, d2 can be 0.01, 0.03, 0.05, 0.07, 0.09, 0.11, 0.13, 0.15, 0.17, 0.19, 0.21, 0.23, 0.25, 0.27, 0.29, 0.31, 0.33, 0.35, etc., or a range between any two of the above values.
[0121] As an example, e2 can be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, etc., or a range between any two of the above values.
[0122] As an example, f can be 1.9, 2.0, 2.1, etc., or a range between any two of the above values.
[0123] In some embodiments, the first and second ternary materials each independently satisfy one or both of the following conditions: b2 is 0.8-0.9, c2 is 0.01-0.09, d2 is 0.01-0.19; M2 includes one or more of Al, Mg, Sr, B, Na, K, Sn, Ti.
[0124] In some embodiments, the first and second ternary materials each independently satisfy a molar ratio of nickel element to manganese element of (3-18): 1.
[0125] In this way, the increase in the content of nickel can increase the reversible lithium intercalation capacity of the ternary material, thereby increasing the energy density of the battery cell; at the same time, by controlling the molar ratio of nickel element to manganese element, the manganese element can be used to inhibit cation mixing, stabilize the layered structure, and has a price advantage, so that the safety performance and control cost of the battery cell can be improved on the basis of high energy density.
[0126] As an example, in ternary materials, the molar ratio of nickel to manganese can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, or any range of any two of the above values.
[0127] In some embodiments, the second ternary material satisfies one or more of the following conditions: the molar content of nickel in the second ternary material is higher than the molar content of nickel in the first ternary material; the molar content of cobalt in the second ternary material is higher than the molar content of cobalt in the first ternary material; and the molar content of manganese in the second ternary material is lower than the molar content of manganese in the first ternary material.
[0128] For secondary ternary materials (secondary particles), high nickel content can significantly increase the lithium storage sites in the secondary ternary materials, thereby improving the energy density of the battery cell; high cobalt content can enhance the stability and electronic conductivity of the layered structure of the secondary ternary materials, compensate for the increased resistance caused by the large number of contact interfaces between particles, and thus improve the dynamic performance of the battery cell.
[0129] For the first ternary material (single crystal particles), since manganese has a stable crystal structure, it can give single crystal particles stronger structural stability, which is consistent with the characteristics of single crystal particles themselves, which have no intergranular grain boundaries and focus more on providing long cycle stability. At the same time, the relatively low proportion of nickel and cobalt in the first ternary material can also balance the production cost and the overall stability of the battery cell while ensuring basic performance.
[0130] In some embodiments, the compaction density of the positive electrode film layer at 5000 kg is 3.4 g / cm³. 3 -3.7g / cm 3 This allows for higher energy density in individual battery cells.
[0131] The compaction density of the positive electrode film can be determined using instruments and methods known in the art. For example, the compaction density of the positive electrode film can be measured according to GB / T24533-2009.
[0132] As an example, the compaction density of the positive electrode film layer at 5000 kg is 3.4 g / cm³. 3 3.5g / cm 3 3.6g / cm 3 3.7g / cm 3 Or it can be a range consisting of any two of the above values.
[0133] In some embodiments, the positive electrode tab satisfies one or both of the following conditions: the thickness of the positive electrode current collector is 10-15 μm; the single-sided thickness of the positive electrode film layer is 30-60 μm. Thus, the thickness range can cover the conventional 2C to 4C ternary battery design.
[0134] In the present application, the single-sided thickness of the positive electrode film layer and the thickness of the positive electrode current collector can be measured using a micrometer.
[0135] For example, the thickness of the positive electrode current collector can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc., or a range formed by any two of the above values.
[0136] For example, the single-sided thickness of the positive electrode film layer can be 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, etc., or a range formed by any two of the above values.
[0137] In the present application, the battery cell will be accompanied by Li deintercalation and consumption during the charging and discharging process, and the molar content of Li is different when the battery cell is discharged to different states. In the present application, the molar content of Li in the list of positive electrode active materials is the initial state of the material, i.e. the state before feeding. After the positive electrode active material is applied to the battery system and undergoes charging and discharging cycles, the molar content of Li will change.
[0138] In some embodiments, the positive electrode current collector can use a metal foil or a composite current collector. For example, as a metal foil, an aluminum foil can be used. The composite current collector can include a high polymer material base layer and a metal layer formed on at least one surface of the high polymer material base layer. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a high polymer material base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0139] In some embodiments, the positive electrode film layer can also optionally include a binder. For example, the binder can include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, a fluorine-containing acrylic ester resin.
[0140] In some embodiments, the positive electrode film layer can also optionally include a conductive agent. For example, the conductive agent can include one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers.
[0141] In some embodiments, the battery cell provided herein further comprises a negative electrode, an electrolyte, and a separator. During the charging and discharging of the battery cell, active ions are intercalated and deintercalated between the positive electrode and the negative electrode. The electrolyte serves to conduct ions between the positive electrode and the negative electrode. The separator is disposed between the positive electrode and the negative electrode and serves to prevent short circuiting between the positive electrode and the negative electrode while allowing ions to pass through.
[0142] [The negative electrode] In some embodiments, the negative current collector can be a metal foil or a composite current collector. For example, as the metal foil, a copper foil can be used. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material base layer (e.g., a base layer of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0143] In some embodiments, the negative electrode film layer includes a negative active material, which can be any of the negative active materials known in the art for use in battery cells.
[0144] In some embodiments, the negative active material includes one or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. As an example, the silicon-based material can include one or more of elemental silicon, silicon oxide compound, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy. The tin-based material can include one or more of elemental tin, tin oxide compound, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as negative active materials for battery cells can also be used. These negative active materials can be used alone or in combination of two or more.
[0145] In some embodiments, the negative electrode film layer can further optionally include a binder. The binder can include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0146] In some embodiments, the negative electrode film layer can further optionally include a conductive agent. The conductive agent can include one or more of super conductive carbon, acetylene black, carbon black, ketjen black, carbon dot, carbon nanotube, graphene, and carbon nanofiber.
[0147] In some embodiments, the negative electrode film layer can also optionally include other auxiliary agents, such as thickening agents (e.g., sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li), etc.).
[0148] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder, and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry on a negative electrode current collector, and after processes such as drying, cold pressing, etc., the negative electrode sheet can be obtained.
[0149] [Electrolyte] The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The type of electrolyte is not particularly limited in the present application and can be selected as needed. For example, the electrolyte can be liquid, gel, or all-solid.
[0150] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0151] In some embodiments, the electrolyte salt can include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonylimide, lithium bis-trifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorobisoxalate borate, lithium bisoxalate borate, lithium difluorodioxalate phosphate, lithium tetrafluorodioxalate phosphate.
[0152] In some embodiments, the solvent can include one or more of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclobutane sulfone, dimethyl sulfone, methyl ethyl sulfone, diethyl sulfone.
[0153] In some embodiments, the electrolyte solution can also optionally include an additive. For example, the additive can include a negative electrode film-forming additive, a positive electrode film-forming additive, and can also include an additive capable of improving certain properties of the battery cell, such as an additive for improving the overcharge performance of the battery cell, an additive for improving the high-temperature or low-temperature performance of the battery cell, etc.
[0154] [Separator] The type of separator is not particularly limited in the present application and any known porous structure separator having good chemical stability and mechanical stability can be selected.
[0155] In some embodiments, the material of the separator film can include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride. The separator film can be a single-layer film or a multi-layer composite film, and is not particularly limited. When the separator film is a multi-layer composite film, the materials of the layers can be the same or different, and are not particularly limited.
[0156] In some embodiments, the positive electrode tab, the negative electrode tab, and the separator film can be made into an electrode assembly through a winding process or a stacking process.
[0157] [Battery cell] In some embodiments, the battery cell can include an outer package. The outer package can be used to package the electrode assembly and the electrolyte described above.
[0158] In some embodiments, the outer package of the battery cell can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the battery cell can also be a soft package, such as a pouch-type soft package. The material of the soft package can be plastic, and as plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate, etc. can be listed.
[0159] The shape of the battery cell is not particularly limited in the present application, and it can be cylindrical, square, or any other shape. For example, Figure 1 is a square structure battery cell 5 as an example.
[0160] In some embodiments, referring to Figure 2 , the outer package can include a shell 51 and a cover plate 53. The shell 51 can include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be provided on the opening to close the receiving cavity. The positive electrode tab, the negative electrode tab, and the separator film can be formed into an electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be selected according to specific actual needs.
[0161] The second aspect of the present application provides a battery device including the battery cell 5 of the first aspect of the present application.
[0162] The battery device mentioned in the present application can include one or more battery cell assemblies for providing voltage and capacity. The battery cell assembly can include a plurality of battery cells 5 connected in series, in parallel, or in a mixed connection through a busbar component.
[0163] In some embodiments, the battery cell assembly is generally formed by arranging a plurality of battery cells 5.
[0164] In some embodiments, the battery cell assembly can be a battery module, which is formed by arranging and fixing a plurality of battery cells. As an example, the battery module can be formed by bundling a plurality of battery cells by a cable tie. The number of battery cells 5 included in the battery module can be one or more, and the specific number can be selected according to the application and capacity of the battery module.
[0165] Figure 3 is a battery module 4 as an example. Referring to Figure 3 In the battery module 4, a plurality of battery cells 5 can be arranged in sequence along the length direction of the battery module 4. Of course, they can also be arranged in any other manner. Further, the plurality of battery cells 5 can be fixed by fasteners.
[0166] Optionally, the battery module 4 can also include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.
[0167] In some embodiments, the battery device can be a battery pack, which includes a box body and one or more battery cell assemblies accommodated in the box body. The number of battery modules included in the battery pack can be one or more, and the specific number can be selected according to the application and capacity of the battery pack.
[0168] Figure 4 and Figure 5 is a battery pack 1 as an example. Referring to Figure 4 and Figure 5 In the battery pack 1, a battery box and a plurality of battery modules 4 arranged in the battery box can be included. The battery box includes an upper box body 2 and a lower box body 3, and the upper box body 2 can be arranged on the lower box body 3 to form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0169] In some embodiments, the battery device can also be an energy storage device. The energy storage device includes an energy storage container, an energy storage cabinet, etc.
[0170] In the third aspect of the present application, a power utilization device is provided, which includes the battery cell of the first aspect of the present application or the battery device of the second aspect of the present application. Thus, the battery cell, the battery module, or the battery pack can be used as a power supply of the power utilization device, and can also be used as an energy storage unit of the power utilization device. The power utilization device can include a mobile device (such as a mobile phone, a notebook computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc., but is not limited thereto.
[0171] As the power consuming device, a battery, a battery module, or a battery pack can be selected according to the use requirement thereof.
[0172] Figure 6 The power consuming device is, for example, a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirement of high power and high energy density of the power consuming device, a battery pack or a battery module can be used.
[0173] The device as another example can be a mobile phone, a tablet computer, a notebook computer, or the like. The device usually requires thinning, and a battery can be used as the power source.
[0174] Embodiments Hereinafter, embodiments of the present application will be described. The embodiments described below are exemplary and are for the purpose of explanation of the present application only, and are not to be understood as a limitation of the present application. In the embodiments, the specific techniques or conditions not mentioned are performed according to the techniques or conditions described in the literature in the art or according to the product manual. The reagents or instruments not mentioned by the manufacturer are all conventional products that can be obtained commercially.
[0175] Embodiment 1 (1) Preparation of the positive electrode sheet Positive electrode active material: a first ternary material LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) having a single crystal particle morphology with an average particle size of 2.6 μm, a second ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) having a secondary particle morphology with an average particle size of 9.7 μm, and a lithium-rich manganese-based material 0.6Li2MnO3+0.4LiNi 0.4 Mn 0.5 Co 0.1 O2 having an average particle size of 9 μm.
[0176] The above positive electrode active material, a conductive agent carbon black Super P, and a binder polyvinylidene fluoride were mixed uniformly in an appropriate amount of N-methylpyrrolidone (NMP) at a weight ratio of 97:1.8:1.2 by stirring to form a uniform positive electrode slurry. The positive electrode slurry was coated on both sides of an aluminum foil, and then dried, cold-pressed, slitted, and cut to obtain a positive electrode sheet.
[0177] (2) Preparation of the negative electrode sheet The negative active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickening agent sodium carboxymethyl cellulose (CMC-Na) are mixed in a weight ratio of 96.82:0.53:1.95:0.7 in a deionized water solvent system, and then fully stirred and uniformly mixed. The mixture is coated on two surfaces of a copper foil. The copper foil is dried and then subjected to cold pressing to obtain a negative electrode sheet with a negative electrode film layer.
[0178] (3) Isolation film A polyethylene film with a thickness of 12 μm is selected as the isolation film.
[0179] (4) Preparation of electrolyte In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1 to obtain a mixed solvent. Lithium hexafluorophosphate (LiPF6) is dissolved in the mixed solvent, and stirred uniformly to form an electrolyte with a molar concentration of 1 mol / L.
[0180] (5) Preparation of battery monomer The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, with the isolation film between the positive electrode and the negative electrode to play a role of isolation. A bare battery cell is formed by a winding process. The bare battery cell is placed in an outer package, and the prepared electrolyte is injected. The battery monomer is obtained after packaging and sealing.
[0181] Examples 2-17 The preparation method of the battery in Examples 2-17 is the same as that in Example 1, and the specific parameter differences are shown in Table 1.
[0182] Table 1
[0183] Note: In Table 1, the chemical formula of NCM9055 is LiNi 0.9 Co 0.05 Mn 0.05 O2.
[0184] Comparative Examples 1-3 Comparative Example 1 differs from Example 1 in that an equal amount of lithium-rich manganese-based material is replaced by an equal amount of ternary material. The mass ratio of the first ternary material to the second ternary material in the replaced ternary material is the same as that in Example 1.
[0185] Comparative Example 2 differs from Example 1 in that an equal amount of single-crystal particle-shaped first ternary material is replaced by an equal amount of secondary particle-shaped second ternary material.
[0186] Comparative Example 3 differs from Example 1 in that an equivalent amount of the second ternary material in the form of secondary particles replaces an equivalent amount of the first ternary material in the form of single-crystal particles.
[0187] Material characterization and battery performance testing (1) Average particle size of primary particles of the lithium-rich manganese-based material Test method: Obtain a cross-section in the thickness direction of the positive electrode sheet, and use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain a scanning electron micrograph of the cross-section of the positive electrode sheet. Observe 10 primary particles of the same size and shape in any region of the same scanning electron micrograph at a magnification of 30000 times. Then subdivide each of the 10 regions into four corners and a center, for a total of five positions. Select the particle size of any one primary particle at each position at this magnification, and take the average of the particle size at the five positions to obtain the average particle size of the primary particles in that region. Then take the average of the particle sizes of the primary particles in the 10 regions to obtain the average particle size of the primary particles. The diameter of the equivalent circle of each particle is taken as the particle size of the particle.
[0188] A scanning electron micrograph of the lithium-rich manganese-based material particles is obtained by scanning the cross-section in the thickness direction of the positive electrode sheet of Example 1, as shown in Figure 7 . Figure 8 A Figure 7 local enlarged view of region A in .
[0189] As can be seen from Figure 7 , the single lithium-rich manganese-based material is an agglomerate of multiple primary particles. At the same time, the particle size of the primary particles in region A is measured to obtain the average particle size of the primary particles of the lithium-rich manganese-based material. Figure 8
[0190] (2) DC internal resistance DCR test: At 25°C, the battery is charged at 1 / 3C constant current to a cutoff voltage of 4.3V, and then charged at 4.3V constant voltage to a current of 0.05C. At this time, the battery is fully charged. After the fully charged battery is left standing for 5 min, it is discharged at a current of 1 / 3C to a state of charge of 10% SOC, and the voltage U1 is recorded. Then, it is discharged at a current of 4C for 30 s, and the voltage U2 is recorded. The DC internal resistance DCR of the battery is calculated as (U2-U1) / discharge current.
[0191] (3) Energy density test: Before testing, the mass of the battery is measured. At 25°C, the secondary battery is charged at a current of 1 / 3C constant current and constant voltage to 4.3V, and then charged at 4.3V constant voltage to a current of 0.05C. After standing for 30 min, it is discharged at a current of 1 / 3C to 2.8V, and the discharge capacity E of the secondary battery is recorded. The energy density of the battery is calculated as E / mass of the battery.
[0192] (4) Cycle performance: at 25°C, first let the battery stand for 2h, then charge to 4.3V at a current of 1 / 3C, then charge to a current of 0.05C at a constant voltage of 4.3V, stand for 10min, then discharge to 2.8V at a current of 1C, record the discharge capacity SOH of the secondary battery. The above is one cycle, repeat the above steps until the discharge capacity decays to 80% SOH, record the cycle number as the cycle life.
[0193] The battery performance test results of Examples 1-17, Comparative Example 1-Comparative Example 3 are shown in Table 2.
[0194] Table 2
[0195] As can be seen from Table 2, the batteries obtained in Examples 1-17 have both high energy density and good kinetic performance. Examples 1-17 combine the first ternary material with single crystal particle morphology, the second ternary material with secondary particle morphology, and the lithium-rich manganese-based material with secondary particle morphology, forming a good particle size grading relationship; at the same time, the lithium-rich manganese-based material with secondary particle morphology can provide more lithium storage sites and a wider working voltage window, improve the ion transport kinetics in the low potential interval, so that the battery monomer has both high energy density and good kinetic performance.
[0196] In contrast, Comparative Example 1 does not contain a lithium-rich manganese-based material, and the direct current resistance DCR is large, resulting in a battery monomer with poor kinetic performance compared to Examples 1-17.
[0197] Comparative Example 2 does not contain a first ternary material with single crystal particle morphology, resulting in a battery monomer with poor cycle performance compared to Examples 1-16. At the same time, although the cycle life of Example 17 is poorer than that of Comparative Example 2, the battery monomer of Example 17 uses LiNi 0.9 Co 0.05 Mn 0.05 O2, and the battery monomer of Example 17 has a higher energy density.
[0198] Comparative Example 3 does not contain a second ternary material with secondary particle morphology, resulting in a high proportion of small particles in the positive active material system, poor dispersion of the positive active material, and easy agglomeration of particles due to high surface energy, resulting in the ion transport path between particles being segmented and discontinuous, reducing ion transport efficiency, and thus resulting in a battery monomer with poor kinetic performance compared to Examples 1-17.
[0199] Note that the present application is not limited to the above-described embodiments. The above-described embodiments are merely examples, and embodiments having substantially the same configuration, function, and effect as the technical idea of the present application are included in the technical scope of the present application. Furthermore, other modes constructed by applying various modifications to the embodiments, or by combining part of the configurations of the embodiments, which can be conceived by those skilled in the art, without departing from the spirit of the present application, are also included in the scope of the present application.
Claims
1. A battery cell, characterized by, The positive electrode sheet comprises: a positive electrode current collector; a positive electrode film layer on at least one side of the positive electrode current collector; the positive electrode film layer comprises a positive electrode active material, the positive electrode active material comprises a ternary material and a lithium-rich manganese-based material, the ternary material comprises a first ternary material having a single crystal particle morphology and a second ternary material having a secondary particle morphology, and the lithium-rich manganese-based material is in a secondary particle morphology. The mass ratio of the first ternary material to the second ternary material in the positive electrode film layer is 1:(1-9).
2. The battery cell of claim 1, wherein, The average particle size of the first ternary material is 1.5-3 μm.
3. The battery cell of claim 1, wherein, The average particle size of the second ternary material is 5-15 μm.
4. The battery cell of claim 1, wherein, The average particle size of the primary particles in the lithium-rich manganese-based material is 150-350 nm.
5. The battery cell of claim 4, wherein, The average particle size of the primary particles in the lithium-rich manganese-based material is 200-300 nm.
6. The battery cell of claim 1, wherein, The average particle size of the lithium-rich manganese-based material is 6-12 μm.
7. The battery cell of any one of claims 1-6, wherein, The positive electrode active material satisfies one or both of the following conditions: The Dv50 particle size of the positive electrode active material in the positive electrode film layer is 3-15 μm; The (Dv90-Dv10) / Dv50 of the positive electrode active material in the positive electrode film layer is 1.6-2.
8. The battery cell of claim 7, wherein, The positive electrode active material satisfies one or both of the following conditions: The Dv50 particle size of the positive electrode active material in the positive electrode film layer is 5-10 μm; The (Dv90-Dv10) / Dv50 of the positive electrode active material in the positive electrode film layer is 1.7-1.
9.
9. The battery cell of any one of claims 1-6, wherein, The mass ratio of the lithium-rich manganese-based material to the ternary material is 1:(1-49).
10. The battery cell of any one of claims 1-6, wherein, The lithium-rich manganese-based material satisfies the chemical formula X.Li2MnO3+(1-X).Li a1 Ni b1 Mn d1 M1 e1 O2; wherein, 0.4≤X<1.0, b1 is 0.2-0.7, d1 is 0.3-0.8, e1 is 0-0.5, b1+d1+e1=1, a1 is 0.6-1.2, M1 includes one or more elements of IA group, IIA group, IIIA group, IVA group, VA group, VIA group, VIII group, IB group, IIIB group, IVB group, VB group, and VIB group.
11. The battery cell of claim 10, wherein, The lithium-rich manganese-based material satisfies one or both of the following conditions: X is 0.6-0.8, b1 is 0.3-0.6, d1 is 0.5-0.7, and e1 is 0-0.2; M1 comprises one or more elements selected from Co, Al, Mg, Sr, B, S, Ca, Na, Sn, Cu, Ti, Nb, La, Bi, Zr, Ga, W, V, Zn, In, Ru.
12. The battery cell of claim 10, wherein, The lithium-rich manganese-based material comprises an inner core and a coating layer, the coating layer covering at least part of the surface of the inner core; the coating layer comprises one or more of a fast ion conductor material and an aluminum-based inorganic material.
13. The battery cell of claim 12, wherein, The thickness of the coating layer is 0.1-1 μm.
14. The battery cell according to claim 12 or 13, characterized in that, The coating layer satisfies one or both of the following conditions: The fast ion conductor material comprises one or more of lithium silicate, lithium nitride, lithium borate, lithium fluoride, lithium carbonate, lithium hydroxide, lithium phosphate, lithium zirconate, lithium sulfate, lithium iodate, lithium sulfide, lithium phosphide, lithium acetate, lithium chloride, lithium bromide, lithium iodide, and lithium phosphorus sulfide; The aluminum-based inorganic material comprises one or more of aluminum oxide, magnesium aluminum spinel, calcium aluminate, aluminum phosphate, aluminum borate, aluminum silicate, aluminum fluoride, sodium hexafluoroaluminate, titanium dialuminate, and aluminum carbide.
15. The battery cell of any one of claims 1-6, wherein, the first and second ternary materials each independently satisfy the chemical formula Li a2 Ni b2 Co c2 Mn d2 M2 e2 O f wherein a2 is 0.6-1.1, b2 is 0.5-0.95, c2 is 0.01-0.25, d2 is 0.01-0.35, e2 is 0.001-0.01, f is 1.9-2.1, b2+c2+d2+e2=1, and M2 includes one or more elements selected from Al, Mg, Sr, B, Ca, Na, K, Sn, Cu, Ti, Nb, La, Bi, and Zr.
16. The battery cell of claim 15, wherein, The first ternary material and the second ternary material each independently satisfy one or both of the following conditions: b2 is 0.8-0.9, c2 is 0.01-0.09, and d2 is 0.01-0.
19. M2 comprises one or more elements of Al, Mg, Sr, B, Na, K, Sn, Ti.
17. The battery cell of any one of claims 1-6, wherein, The first and second ternary materials each independently satisfy a molar ratio of nickel element to manganese element of (3-18):
1.
18. The battery cell of any one of claims 1-6, wherein, The second ternary material satisfies one or more of the following conditions: The molar content of nickel element in the second ternary material is higher than the molar content of nickel element in the first ternary material; The molar content of cobalt element in the second ternary material is higher than the molar content of cobalt element in the first ternary material; The molar content of manganese element in the second ternary material is lower than the molar content of manganese element in the first ternary material.
19. The battery cell of any one of claims 1-6, wherein, The compacted density of the positive electrode film layer at 5000kg is 3.4g / cm 3 - 3.7g / cm 3 .
20. The battery cell of any one of claims 1-6, wherein, The positive electrode sheet satisfies one or both of the following conditions: The thickness of the positive electrode current collector is 10-15 μm; The single-sided thickness of the positive electrode film layer is 30-60 μm.
21. A battery device, characterized by A plurality of battery cells according to any one of claims 1-20.
22. An electrical device, comprising: A battery device according to claim 21.
Citation Information
Patent Citations
Positive electrode slurry, positive electrode plate, battery cell, battery monomer, battery and electric device
CN115832277A
Preparation method of high-performance cobalt-free lithium-rich positive electrode material
CN118026283A
Positive electrode material and preparation method thereof, positive electrode plate and secondary battery
CN118299540A
Modified lithium-rich manganese-based material, modification method of lithium-rich manganese-based material, secondary battery and electric device
CN118511312A
Positive active material and preparation method thereof, positive pole piece, secondary battery, battery module, battery pack and electric device
CN118613932A